The critical success factors of e-CRM implementation in Saudi companies / Mazen Abdul Jabbar - Jabbar, Mazen Abdul (2011)
Electronic Customer Relation Management (e-CRM) is a new marketing tool that is widely used by organizations in various domains such as business, education and government agencies. One of the most important functional areas of e-CRM is in managing the organization's customers. However, the implementations of e-CRM in organizations are plagued by the high failure rate. This research is aimed to identify the critical success factors of e-CRM implementation that would lead to successful e-CRM implementation projects in organizations. A total of 12 critical success factors are investigated in this research and these are categorized under four main dimensions, which are technology, organization's climate, customer and consultant. The scope of this study is e-CRM implementation in Saudi Arabia as currently there are many such implementation projects in the kingdom. This research was conducted in three stages, which addressed different research objectives and the outcome from one stage was used in the next stage until all the research objectives were achieved. The first stage involves reviewing the literature on the field of customer relation and customer relation management and the related theories. This stage provides a clear understanding of the factors and issues that influenced CRM implementation in organizations. It discusses e-CRM definitions from various perspectives and the challenges as well as the implementation barriers. A qualitative study was also conducted to explore the e-CRM implementation factors in organizations. The outcome of the qualitative study and related literature analysis was used in the second stage to derive the framework for e-CRM implementation. Findings from in-depth interviews, focus group discussions, and content analysis of successful e-CRM implementation experiences were used to generate the factors that were likely to influence the e-CRM implementation with the four specified dimensions. The guiding principle and the components of success were the two additional factors introduced in the current model, and these have not been studied in e-CRM implementation research within the context of Saudi Arabia. Empirical analysis was conducted in the third and last stages of the study in order to validate the critical success factors for e-CRM implementation in Saudi organizations. Three instruments with a total of 120 items are used to gather data of e-CRM implementation from organizations, customers, and consultants. The telecommunication and the banking sectors were selected to test the model. The study established that the organization is the most important dimension in the implementation process. When comparing the findings, e-CRM implementation for SAMBA Bank is better compared to the National Commercial Bank (Alahli Bank) and the rest of the other companies in this study. E-CRM of the banking sectors appear to be widely used by Saudi citizens than the telecommunication sector. In addition, the findings indicate that the average ratio of e-CRM implementation success in Saudi companies is 73.92%, which is a relatively high achievement rate. A total of 5 critical success factors are identified to influence the e-CRM implementation and these are leadership, component of success, customer awareness, customer understanding, and collaboration. Based on the researcher's opinion, functionality and project management are two factors which are believed to influence the e-CRM although these are not statistically approved. Cost and benefits analysis and experience are two variables which are believed to have low impact to e-CRM implementation. A total of 3 critical success factors are found to have no effect on the e-CRM implementation and these are the way the e-CRM was developed, customer willingness to adopt the internet culture and the guiding principles. The model of e-CRM implementation in Saudi companies is then derived as a clear guidance for the implementation process. A robust, valid and reliable scale is also developed in this research that can be used by academician for future research or by the industry to measure the success of the implementation process.